Electrostatic charge injection for reusing face masks: Mechanisms, performance, and a household alternative - Peng, Zehua; Li, Zhiyuan; Huang, Xingcan; Yu, Xinge; Leung, Michael K. H.; Wang, Zuankai; Yang, Zhengbao (EcoMat (Beijing, China), 2024)
The COVID‐19 pandemic underscores the effectiveness of face masks in combating respiratory infectious diseases and the importance of adequate supply. However, the widespread use of disposable masks has led to severe environmental pollution. In this study, we propose a two‐step strategy for mask reuse, aimed at both mitigating mask waste pollution and improving mask availability in future epidemic outbreaks. Our strategy involves disinfection and corona charging processes, enabling surgical masks to maintain a filtration efficiency of 88.7% even after five cycles of reuse. We highlight the crucial role of volume charges over surface charges in maintaining filtration performance stability and durability, and we visualize the underlying mechanisms using energy band diagrams and potential well models. Additionally, we introduce a simple household solution for simultaneously drying and charging, making it accessible for widespread use. Our research offers a viable strategy for promoting environmental sustainability and alleviating mask supply pressures during significant public health crises. Disposable face masks pose significant environmental concerns due to their non‐biodegradable nature and contribution to microplastic pollution. This research explores sustainable practices for mask reuse, emphasizing effective disinfection and charge replenishment techniques. We have demonstrated that volume charges, particularly those deeply embedded within the forbidden band introduced by a high corona bias, significantly enhance the stability and durability of filtration.